Legislative acts, presidential issuances, and judicial rulings pertaining to the University of the Philippines an annotated compilation - Ferrer, Resurreccion N., 1937-
A historico-chronological approach sets the pace and tempo of this study, from the passage of the University Charter up to 1978. In the process were examined closely pertinent legislative enactments such as Acts (so-called Public Laws), Commonwealth Acts, Republic Acts, and Presidential Decrees. Other issuances from the Chief Executive were also looked into, like Executive Orders, Administrative Orders, Proclamations, and Letters of Instructions.